2015
DOI: 10.1017/s0967199415000015
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of recombinant human insulin-induced maturational events inClarias batrachus(L.) oocytesin vitro

Abstract: Regulation of insulin-mediated resumption of meiotic maturation in catfish oocytes was investigated. Insulin stimulation of post-vitellogenic oocytes promotes the synthesis of cyclin B, histone H1 kinase activation and a germinal vesicle breakdown (GVBD) response in a dose-dependent and duration-dependent manner. The PI3K inhibitor wortmannin abrogates recombinant human (rh)-insulin action on histone H1 kinase activation and meiotic G2-M1 transition in denuded and follicle-enclosed oocytes in vitro. While the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…Besides, insulin/IGF1 stimulation of meiotic G2-M1 transition in Xenopus and zebrafish oocytes has been shown to require Akt activation (Andersen et al 2003, Das et al 2013. Interestingly, pharmacological inhibition of PI3K could attenuate insulin/Igf1-mediated GVBD response in southern flounder and catfish follicle-enclosed oocytes (Picha et al 2012, Hajra et al 2016. Although growth factor-mediated Akt activation requires receptor tyrosine kinase activation, MIS regulation of Akt phosphorylation may primarily involve activation of GPCR in oocytes (Sadler & Ruderman 1998, Pace & Thomas 2005.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, insulin/IGF1 stimulation of meiotic G2-M1 transition in Xenopus and zebrafish oocytes has been shown to require Akt activation (Andersen et al 2003, Das et al 2013. Interestingly, pharmacological inhibition of PI3K could attenuate insulin/Igf1-mediated GVBD response in southern flounder and catfish follicle-enclosed oocytes (Picha et al 2012, Hajra et al 2016. Although growth factor-mediated Akt activation requires receptor tyrosine kinase activation, MIS regulation of Akt phosphorylation may primarily involve activation of GPCR in oocytes (Sadler & Ruderman 1998, Pace & Thomas 2005.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of the PI3K/Akt/PDE3 cascade in the downregulation of intra-oocyte cAMP level concomitant with PKA inactivation has been reported previously in fish and amphibian oocytes (Andersen et al, 2003;Pace and Thomas, 2005b;Das et al, 2013;Maitra et al, 2014). Moreover, the inhibition of PI3K has been shown to promote PKA activation that in turn successfully attenuates insulin-induced meiotic G2-M1 transition in catfish follicle enclosed oocytes in vitro (Hajra et al, 2016). Furthermore, studies in somatic cancer cells Figure 5 Proposed model for rapid activation of intra-oocyte signalling cascades in maturational steroid (DHP)-stimulated zebrafish oocytes and cross-talk between cAMP-mediated and PI3K/Akt-and MEK/MAPK-dependent signalling events.…”
Section: Discussionmentioning
confidence: 54%
“…Previously, we have shown that inhibition of either AC or PKA by pharmacological inhibitors alone is sufficient to promote a GVBD response even without hormonal stimulation in this species (Maitra et al ., 2014; Das et al ., 2016a). Furthermore, PKA inhibition alone has been found to remove meiotic arrest independent of MIS stimulation in various other teleosts (Haider & Baqri, 2002; Khan & Maitra, 2013; Hajra et al ., 2016). Taken together these data indicate that downregulation of cAMP/PKA signalling in teleost oocytes plays a critical role in the process of MPF activation and the GVBD response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main purpose of antibiotics in the perioperative period is to prevent surgical site infection, but attention to aseptic operation, gentle operation and thorough hemostasis during surgery are more important than antibiotics to prevent infection; sometimes antibiotics are used for the doctor's psychological comfort or the patient's request. Clinically, antibiotics are not necessary to prevent infection for some clean and near-clean operations with less trauma [14] , and it has become a consensus that antibiotics should not be used in the perioperative period of a class of incisions such as inguinal hernia surgery, thyroid surgery and craniocerebral surgery, also reported in the literature [15,16] . With the standardization of the use of antibiotics in clinical work, there are reports that antibiotics are not used in the second type of incision such as gallbladder surgery and appendix surgery and even some third type incisions such as abscess drainage surgery may not use antibiotics.…”
Section: Group Experimental Group Control Groupmentioning
confidence: 99%